COMPARISON OF THE EFFECTIVENESS OF GIVING BINAHONG LEAF (Anredera cordifolia (Ten) Steenis) AND PAPAYA LEAF (Carica papaya) ON SKIN WOUND HEALING IN WHITE RAT (Rattus novergicus) - Winarjo, Givenchy A; Arifin, Fransiscus; Oenarta, Dave G (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: The incidence of acute and chronic injuries increases every year. Most injuriesin the world population, as many as 48%, are caused by trauma or surgery. the highestincidence of wounds in the world based on the etiology was from surgery, which was 110.30million cases. One of the handlings of wounds on the skin can be done by giving herbalmedicines, which can be easily accessed by the public, such as binahong leaves and papayaleaves. Purpose: To analyze the effectiveness of giving 40% binahong leaf extract cream and 40%papaya leaf extract cream on the wound distance in the white rat wound healing process. Method: this study is an experimental study with post-test only control group designapproach. The sampling technique used in this study was a random sampling method wherethe number of samples was calculated using the Federer formula, with a total sample of 28white rats. The distance of the wound was measured using a micrometer. Results: Twenty-eight wound distance on rats were measured as subjects of the study andthen treated with binahong leaf extract cream and papaya leaf extract cream, then the wounddistance of each treatment was measured using a micrometer. According to the results, 40%binahong leaf extract cream and 40% papaya leaf extract cream showed better effectivenessin reducing the wound distance of white rat incision than the negative control group (creambase) and positive control group (gentamicin ointment). According to the Mann Whitney testcomparing the P1 group (40% binahong leaf extract cream) and P2 (40% papaya leaf extractcream), p-value >0.05, which is 0.543, which means that P1 has no significant meandifference with P2. Conclusion: There was no significant difference in effectiveness between the treatment of40% binahong leaf extract cream and 40% papaya leaf extract cream.